Awareness of Islamic English among Muslim students in Malaysia - Adam, Zalika; Parveen Lallmamode , Sheila (2009)

(untitled)
Abstract This paper adopts a critical examination of the Americano-Eurocentric perspective of the teaching of the English Language in the Muslim world. With globalization and the spread of English, language textbooks written in L1 countries have been exported in the guise of ‘authentic English’ (Cook, 1999) to many Muslim countries around the world. This study attempts to investigate the awareness of Islamic English among Muslim students studying in Muslim countries. Three main problems that occur when Muslims are encouraged to mimic L1 non-Muslim native speakers, and discourse in the English language, are investigated: (1) distortion in transliteration; (2) distortion in translation; (3) use of islamically inappropriate vocabulary and etiquettes in one’s discourse. Questionnaires were collected from 31 university ESL students in Malaysia. The overall results show that Muslim students are very motivated to acquire English for work and research purposes. However, some students fell into problems related to distortions in translation and transliteration because their knowledge of the Arabic language and the religion of Islam as a consequence, are weak. Muslims linguists are encouraged to develop ELT textbooks and teaching materials, with the help of an Islamic English corpus, for all Muslim students worldwide.